The role of lake morphometry in modulating surface water carbon concentrations in boreal lakes - Joan P Casas-Ruiz; Julia Jakobsson; Paul A del Giorgio (Environmental Research Letters, 2021)
Earth’s lakes vary greatly in size and morphometry, from small circular lakes of hundreds of m ^2 to large and deep fractal systems of several thousands of km ^2 . Previous research has demonstrated a link between the size of lakes and their carbon dynamics. However, the influence of lake morphometry on lake carbon biogeochemistry remains largely unexplored. Here, we analyze the morphometry and carbon concentrations of more than 250 lakes across boreal Quebec, encompassing a wide range in lake size from 0.002 to 4300 km ^2 . We show that, in addition to lake size, the biogeochemistry of lake carbon is influenced by the circularity, shoreline complexity and vertical profile of the lake. Yet the type and degree of influence vary among the different carbon species. A comparative exercise shows that taking into account the morphometry of lakes moderately increases the predictive power of empirical models of carbon concentration across lakes. Therefore, future studies might benefit from adding lake morphometry metrics to the empirical rules used for prediction and upscaling.